Characterization of Rhinodrilus alatus hemoglobin (HbRa) and its subunits: Evidence for strong interaction with cationic surfactants DTAB and CTAC - Carvalho, Francisco A. O.; Carvalho, Jose W. P.; Biazin, Ezer; Santiago, Patricia S. [UNESP]; Tabak, Marcel (Elsevier B.V., 2014)
Rhinodrilus alatus is an annelid and its giant extracellular hemoglobin (HbRa) has a molecular mass (MM) of 3500 kDa. In the current study, the characterization of MM values of the HbRa subunits, and the effects of surfactants and alkaline pH upon HbRa stability were monitored. Electrophoresis, MALDI-TOF-MS and ADC show that the MM values of HbRa subunits are very close, but not identical to the Glossoscolex paulistus hemoglobin (HbGp). The monomer d is found to exist in, at least two isoforms: the main one, d(1) displays a MM of 16,166 +/- 16 Da, and the second one, d(2), is less intense with MM of 16,490 +/- 20 Da. For the trimer abc and tetramer abcd, single contributions around 51,470 Da and 67,690 Da were observed, respectively. Finally, the monomers a, b, and c, present MM values of 17,133, 17,290 and 15,506 Da, respectively. Both CTAC and DTAB interact strongly with HbRa, and up to seven surfactant molecules are bound to the protein. On the other hand, spectroscopic studies show that HbRa is more stable at alkaline pH, as compared to HbGp. Thus, our data suggest that alkaline medium, up to pH 10.0, induces the oligomeric dissociation, without promoting the subunits unfolding and heme iron oxidation. Our results suggest that the MM of the annelid hemoglobin subunits is conserved to a great extent in the evolution process of these species. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Extracellular hemoglobin; Rhinodrilus alatus; Subunit masses; MALDI-TOF-MS; Cationic surfactants